SLANG WORDS OF MOVIE CLUELESS - Sari, Dewi Purnama; Syaputri, Komala Dwi; Hajiriah, Anggi (Jurnal Ilmiah Bina Bahasa, 2023)
Slang, as a linguistic phenomenon, serves as a means of informal communication within specific communities. This study delves into the analysis of slang usage in the film "Clueless." The primary objectives are to identify the various word formation processes employed and the functional roles of slang among the characters. Focused on the 2018 production of "Clueless" by John Francis Daley and Jonathan Goldstein, this research adopts a library-based approach using descriptive qualitative methods. Data collection involves documenting slang instances from the movie script, followed by a systematic tabulation and theoretical framework explanation. The analysis employs perspectives on word formation processes and the functional dynamics of slang. Findings reveal thirty-two distinct slangs categorized into six word formation processes and seven functional roles. Additionally, meanings are inferred through contextual understanding and reference to dictionaries. This study contributes to understanding the intricacies of slang usage in contemporary media narratives.